2013
DOI: 10.1158/0008-5472.can-12-2130
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Deleting Cancer-Associated Fibroblasts in Cholangiocarcinoma

Abstract: Cancer associated fibroblasts (CAF) are abundant in the stroma of desmoplastic cancers where they promote tumor progression. CAF are `activated' and as such may be uniquely susceptible to apoptosis. Using cholangiocarcinoma (CCA) as a desmoplastic tumor model, we investigated the sensitivity of liver CAF to the cytotoxic drug navitoclax, a BH3 mimetic. Navitoclax induced apoptosis in CAF and in myofibroblastic human hepatic stellate cells, but lacked similar effects in quiescent fibroblasts or CCA cells. Unlik… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
164
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 171 publications
(166 citation statements)
references
References 44 publications
2
164
0
Order By: Relevance
“…Although not related to EMT, a recent study [142] showed the possibility of targeting CAFs in a syngeneic rat model with a pro-apoptotic drug called Navitoclax, which suppressed tumor growth and improved host survival. Therefore, efforts should be directed to the development of targeted therapies against both tumor cells and their interactions with the surrounding stroma, in order to reduce metastasis and improve patient conditions.…”
Section: Tumor-associated Macrophages (Tams) and Mast Cells (Figure 3b)mentioning
confidence: 99%
“…Although not related to EMT, a recent study [142] showed the possibility of targeting CAFs in a syngeneic rat model with a pro-apoptotic drug called Navitoclax, which suppressed tumor growth and improved host survival. Therefore, efforts should be directed to the development of targeted therapies against both tumor cells and their interactions with the surrounding stroma, in order to reduce metastasis and improve patient conditions.…”
Section: Tumor-associated Macrophages (Tams) and Mast Cells (Figure 3b)mentioning
confidence: 99%
“…However, achieving effective cancer cell-directed therapy has been challenging because of the diverse alterations in these transformed cells and the continued accumulation of abnormalities due to genomic instability (1,2). In contrast, the tumor stroma appears to be more genetically uniform and represents an additional therapeutic target (1,(3)(4)(5). Exploiting the dependence of cancer cells on the tumor microenvironment will require a further in-depth understanding of the dynamic reciprocal interaction between cancer cells and the surrounding stroma.…”
mentioning
confidence: 99%
“…This dense stroma, which is found in a number of solid tumors, including cholangiocarcinoma, pancreatic cancer, and certain subtypes of breast cancer, has been proposed as a potential target for anticancer therapy (3,6,9,10).…”
mentioning
confidence: 99%
See 2 more Smart Citations